PERAN KOMUNIKASI ANTAR PRIBADI PIMPINAN DALAM MENINGKATKAN MOTIVASI KERJA ANGGOTA PANGKALAN TNI ANGKATAN UDARA SOEWONDO MEDAN - Tua, Raja Maruli; Lubis, Suwardi; Silviani, Irene (LPPM Universitas Darma Agung, 2020)
Interpersonal communication is sending messages from one person to another person with a direct reciprocal nature. Likewise with Soewondo Air Force Base, the role of leadership is crucial as an engine of organization through understanding the problems that occur.This study aims at finding how the interpersonal communication role of the leadership of the Soewondo air Force base work unit towards its members, how the work motivation of members is and how the interpersonal communication role of the leadership influential in increasing the work motivation of members. The problem of several violations of the law was found so that it affects work motivation. Through the interpersonal communication approach, a leader can create an interest in himself of creating an atmosphere that can invite members to conduct interpersonal communication in the hope of providing solutions to the problems faced by their members so as to obtain maximum work result. In can be said that he role of interpersonal communication of leaders to members of the Suwondo Medan Lanud work unit in general is good, the motivation of Medan Suwondo Lanud members in general is good, interpersonal communication of leaders partially gives a significant influence on the work motivation of members of the Soewondo Lanud. From the observations in the preliminary part of this study it is also very suitable, namely the finding of several members who are experiencing legal problems that result in decreased work motivation and obstructed work done.